Effects of Water, Sanitation, and Hygiene on the School Absenteeism of Basic Level Students in the Government School of Nepal - Sharma, Mohan Kumar; Adhikari, Ramesh (Frontiers in Education, 2022)
This study assesses the effect of improved water, sanitation, and hygiene (WASH) services on students’ absenteeism in government basic schools for 10–19 years old in Nepal. This study applied an ex post facto research design on two groups of students: with and without improved school WASH services. This study showed that students in schools with improved WASH services were more likely to be regular in attendance (80%) compared to those without (58%), p < 0.001. There was an association between students’ school absenteeism and student grades, p < 0.05. Moreover, the caste, religion, and grades of students were also associated with students’ school absenteeism, p < 0.001. The analysis further showed that students with improved WASH were more likely to be regular [crude odds ratios (COR) = 0.353; 95% confidence interval (CI); 0.256–0.487, p < 0.001] than those without. This trend was maintained across all demographics. It was significant even after the inclusion of all sociodemographic characteristics and increased rapidly [adjusted odds ratio (AOR) = 0.508; 95% CI; 0.334–0.773, p < 0.01]. The Brahmin/Chhetri-Terai and the Dalit students were more likely to be absent (COR = 0.315; 95% CI; 0.153–0.648, p < 0.01 and AOR = 0.274; 95% CI; 0.139–0.542, p < 0.001, respectively) than Brahmin/Chhetri-Hill, Janajati, and other castes. This study underscores the importance of WASH services in schools in reducing students’ school absenteeism. Access to WASH services is recommended with several awareness programs to reduce absenteeism and increase students’ school regularity.